'We are still quite patchy about what we know' International migration and the challenges of definition, categorisation and measurement on local service provision. Issue 15 (18th November 2021) - Devanney, Carol; Lloyd, Anthony; Wattis, Louise; Bell, Victoria
ABSTRACT: International migration has a consistently high profile within national and international politics with increased focus on measurement and quantification of migrant numbers, impact on services and contribution to local, regional and national economies. However, the absence of consistency within definitions, categorisations and measurement of international migration and migrant populations create challenges and barriers to both understanding the needs of migrant communities but also the provision of adequate services within specific geographical areas. This paper will present findings from a project designed to map the impact of migration on a settled community within a Local Authority (LA) in the North East of England. As the project encountered routine inconsistencies around definitions, categorisations and measurement of migration within the LA area, this paper demonstrates the complexity of trying to 'measure' migration on the ground and while consistency in measurement is key to accurate data, we conclude with an ethical question about the rationale for collecting data on migrant populations.